Modeling yield, cost, and quality of an NoC with uniformly and non-uniformly distributed redundancy - Shamshiri, Saeed; Kwang-Ting Cheng (2010 28th VLSI Test Symposium (VTS), 2010)
In this paper, we propose a quality metric for an NoC and model the yield and cost of a spare-enhanced multi-core chip subject to a given quality constraint. Our experiments show that the overall quality of a mesh-based NoC depends more on the reliability of the inner links than the outer links; therefore, a non-uniform distribution of spare wires could be more effective and cost efficient than a uniform approach.